Studi Eksperimental Pengaruh Parameter Pengeboran terhadap Karakteristik Burr pada Pengeboran Tulang Kortikal - Arzaq Guruh Dityamri Arzaq; Gusri Akhyar Ibrahim; Muh Thohirin; Wisnaningsih; Syaipudin Anwar; An-Nisa Magnolia (Universitas Muhammadiyah Metro, 2026)
Cortical bone drilling represents an initial stage in orthopedic surgical procedures prior to implant screw insertion, where the quality of the drilled hole is strongly influenced by burr formation along the hole edges. Excessive burrs may increase the risk of tissue trauma, interfere with screw placement, and elevate the likelihood of postoperative complications. This study aims to investigate the effects of drilling parameters on burr characteristics during cortical bone machining and to determine the optimal parameter conditions that minimize burr formation. The research was conducted experimentally using fresh bovine cortical bone specimens and employed a Response Surface Methodology (RSM) experimental design. The investigated parameters included spindle speeds of 500, 1000, and 1500 rpm, feed rates of 35, 60, and 85 mm/min, and cooling conditions consisting of NaCl solution, Opsite Spray, and dry drilling. Drilling experiments were performed using a three-axis CNC machine, while burr characteristics were visually evaluated using a USB microscope. The results indicate that feed rate is the most influential parameter affecting burr formation, followed by spindle speed and cooling condition. Drilling conditions characterized by low feed rates, high spindle speeds, and the application of cooling fluids either NaCl solution or Opsite Spray produced smaller burrs and smoother hole-edge morphologies. The optimal condition was achieved through a specific combination of parameters that minimized burr formation, thereby demonstrating potential improvements in hole quality and procedural safety during cortical bone drilling.